Double-letter processing in surface dyslexia and dysgraphia following a left temporal lesion: A multimodal neuroimaging study. (December 2015) - Tomasino, Barbara; Marin, Dario; Maieron, Marta; D'Agostini, Serena; Fabbro, Franco; Skrap, Miran; Luzzatti, Claudio
Abstract: Neuropsychological data about acquired impairments in reading and writing provide a strong basis for the theoretical framework of the dual-route models. The present study explored the functional neuroanatomy of the reading and spelling processing system. We describe the reading and writing performance of patient CF, an Italian native speaker who developed an extremely selective reading and spelling deficit (his spontaneous speech, oral comprehension, repetition and oral picture naming were almost unimpaired) in processing double letters associated with surface dyslexia and dysgraphia, following a tumor in the left temporal lobe. In particular, the majority of CF's errors in spelling were phonologically plausible substitutions, errors concerning letter numerosity of consonants, and syllabic phoneme-to-grapheme conversion (PGC) errors. A similar pattern of impairment also emerged in his reading behavior, with a majority of lexical stress errors (the only possible type of surface reading errors in the Italian language, due the extreme regularity of print-to-sound correspondence). CF's neuropsychological profile was combined with structural neuroimaging data, fiber tracking, and functional maps and compared to that of healthy control participants. We related CF's deficit to a dissociation between impaired ventral/lexical route (as evidenced by a fractional anisotropy – FA decrease along the inferior fronto-occipital fasciculus – IFOF) and relatively preserved dorsal/phonological route (as evidenced by a rather full integrity of the superior longitudinal fasciculus – SLF). In terms of functional processing, the lexical-semantic ventral route network was more activated in controls than in CF, while the network supporting the dorsal route was shared by CF and the control participants. Our results are discussed within the theoretical framework of dual-route models of reading and spelling, emphasize the importance of the IFOF both in lexical reading and spelling, and offer a better comprehension of the neurological and functional substrates involved in written language and, in particular, in surface dyslexia and dysgraphia and in doubling/de-doubling consonant sounds and letters.